Seismic structural control using a novel high performance active mass driver system. - Wang, Yen-Po (Earthquake engineering & structural dynamics.)
To resolve difficulties encountered by current technology in structural control against earthquakes, this study proposes a novel high performance active mass driver (HP-AMD) system. Based on an active mass driver system, the device is integrated with a mechanical pulley system for stroke amplification to enhance simultaneously efficiency and save power. Meanwhile, an instantaneous optimal direct output feedback control algorithm is derived alongside the hardware development. Numerical simulation is performed using a five storey steel frame as the object structure under the 1940 El Centro earthquake. To gain further insight into the HP-AMD system, the effects of stroke amplification as well as damper weight on system performance are explored. Analysis results demonstrate that the proposed HP-AMD system is a promising means to improving current active structural control techniques.